Properties of short kenaf fiber-reinforced thermoplastic polyurethane composites - Yousuf, Ali Gumaan El-Shekeil (2012)
This research was carried out to produce a new composite material from kenaf (Hibiscus Cannabinus) bast fiber and thermoplastic polyurethane (TPU/KF). The effect of processing parameters (i.e. temperature, time and speed in the internal mixer) on tensile strength were studied. The effect of different fiber sizes; namely, <125, 125-300, and 300-425 μm on tensile, flexural, and impact strengths and thermogravimetric analysis (TGA) were studied. Fiber loading (i.e. 20, 30, 40 and 50 % fiber by weight) was tested using tensile and flexural properties and impact strength. Further characterizations for the 30% fiber loading using hardness and abrasion resistance were performed. Effect of sodium hydroxide (NaOH) treatment on TPU/KF mechanical properties was determined. Effect of polymeric Methylene Diphenyl Diisocyanate (pMDI) additive on mechanical and thermal properties of TPU/KF composites was also investigated. Effect of pMDI chemical treatment was studied in two procedures. First, fibers were chemically treated with pMDI. Second, pMDI chemical treatment was used with NaOH pretreated fibers. Temperature, time and speed were optimum at 190 °C, 11 min, and 40 rpm, respectively Fiber size and fiber loading were optimum at fibers between 125 and 300 μm and 30% fiber loading. Tensile strength decreased by 37, 47 and 62% for 2, 4 and 6% NaOH concentrations; respectively. Flexural and impact strengths have also deteriorated. These results were supported by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and TGA. It was noticed that the addition of 2, 4 and 6% pMDI did not show a significant change in tensile or thermal properties. These results were also confirmed by FTIR, TGA and Differential Scanning Calorimetry (DSC). pMDI chemical treatment has slightly increased tensile strength, while NaOH+pMDI chemical treatment showed increase in tensile strength and modulus by 30% and 42% respectively, however no significant change was noted in strain. This increase was evident by FTIR, which showed a better H-bonding and SEM which showed a better fiber-matrix adhesion.